ASIAN APRICOT APHID, MYZUS MUMECOLA (MATSUMURA, 1917) (HEMIPTERA: APHIDIDAE), FOUND IN SERBIA (Acta Entomologica Serbica, 2021)
Asian apricot aphid, Myzus mumecola (Matsumura, 1917) (Hemiptera: Aphididae, Aphidinae) has been found during spring of 2021 in many localities in Serbia (Ljig, Smederevo, Velika Plana, Belgrade and Šid) on cultivated apricot. The species is of Asian origin, a few years ago it was found in Italy and in Hungary. Research of the species indicates that it is rapidly widening its distribution in Europe. Damages made to apricot trees by feeding on leaves at young branches and making red galls are significant. Presence, damage and biology of M. mumecola needs to be studied in the future, especially its secondary hosts which are not enough known.